Penolakan Israel terhadap Bantuan Kemanusiaan WCC-EAPPI - Yuanto, Aviarma; Putranti, Ika Riswanti (Journal of International Relations, 2019)
The World Council of Churches (WCC) is an institution that accommodates Christian unity throughout the world. WCC brings together churches, denominations and church fellowships in more than 110 countries and territories throughout the world, representing more than 500 million Christians. As a religious organization, WCC has a program that focuses on humanitarian assistance, named Ecumenical Accompaniment Program in Palestine and Israel (EAPPI). But since 2016, this WCC-EAPPI’s humanitarian assistance has been refused by Israel. This refusal resulted in many losses especially for conflict victims. This research aims to find out the reasons for Israel thatrefuses the existence of WCC-EAPPI humanitarian assistance. By using aspects of the humanitarian diplomacy concepts, it can be explained by the reason that Israel refused WCC-EAPPI humanitarian assistance. In this refusal, it is inseparable from the perspective, performance and principles of the WCC-EAPPI itself. The suitability of WCC-EAPPI activities with humanitarian diplomacy aspects deserves to be highlighted in explaining the refusal obtained from Israel